Identification and expression analysis of TLR2 in mucosal tissues of turbot (Scophthalmus maximus L.) following bacterial challenge. (August 2016) - Liu, Fengqiao; Su, Baofeng; Gao, Chengbin; Zhou, Shun; Song, Lin; Tan, Fenghua; Dong, Xiaoyu; Ren, Yichao; Li, Chao
Abstract: The pathogen recognition receptors (PRRs), which can recognize the conserved pathogen-associated molecular patterns (PAMPs) of the bacteria, play key roles in the mucosal surfaces for pathogen recognition and activation of immune signaling pathways. However, our understanding of the PRRs and their activities in mucosal surfaces in the critical early time points during pathogen infection is still limited. Towards to this end, here, we sought to identify the Toll-like receptor 2 (TLR2) in turbot as well as its expression profiles in mucosal barriers following bacterial infection in the early time points. The full-length TLR2 transcript consists of open reading frame (ORF) of 2451 bp encoding the putative peptide of 816 amino acids. The phylogenetic analysis revealed the turbot TLR2 showed the closest relationship to Paralichthys olivaceus . The TLR2 mRNA expression could be detected in all examined tissues, with the most abundant expression level in liver, and the lowest expression level in skin. In addition, TLR2 showed different expression patterns following Vibrio anguillarum and Streptococcus iniae infection, but was up-regulated following both challenge, especially post S. iniae challenge. Characterization of TLR2 will probably contribute to understanding of a number of infectious diseases and broaden the knowledge of interactions between host and pathogen, which will eventually help in the development of novel intervention strategies for farming turbot. Highlights: A TLR2 was identified in turbot. TLR2 was ubiquitously expressed in turbot tissues. TLR2 was significantly induced after bacterial challenge.